Efficient high performance computing with the ALICE event processing nodes GPU-based farm - Ronchetti, Federico; Akishina, Valentina; Andreassen, Edvard; Bluhme, Nora; Dange, Gautam; de Cuveland, Jan; Erba, Giada; Gaur, Hari; Hutter, Dirk; Kozlov, Grigory; Krčál, Luboš; La Pointe, Sarah; et al. (Frontiers in Physics, 2025)
Due to the increase of data volumes expected for the LHC Run 3 and Run 4, the ALICE Collaboration designed and deployed a new, energy efficient, computing model to run Online and Offline O2 data processing within a single software framework. The ALICE O2 Event Processing Nodes (EPN) project performs online data reconstruction using GPUs (Graphic Processing Units) instead of CPUs and applies an efficient, entropy-based, online data compression to cope with Pb–Pb collision data at a 50 kHz hadronic interaction rate. Also, the O2 EPN farm infrastructure features an energy efficient, environmentally friendly, adiabatic cooling system which allows for operational and capital cost savings.